Mutiny amid Repression Russian Soldiers in the Revolution of 1905-1906 - Bushnell, John (Indiana University Press, 1985)
Deeply religious, steadfast in battle, instinctively deferential to his officers-this was the established image of the Russian soldier at the time of the revolution of 1905. The Russian army's principal role in that upheaval, it is generally believed, was the suppression of civil disorder. Challenging this conventional wisdom, John Bushnell's startling study shows that the army itself was in a state of rebellion.